2017
DOI: 10.1126/scitranslmed.aal3694
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 immunity is protective in metabolic disease but exacerbates NAFLD collaboratively with TGF-β

Abstract: Nonalcoholic fatty liver disease (NAFLD) is now the most common progressive liver disease in developed countries and is the second leading indication for liver transplantation due to the extensive fibrosis it causes. NAFLD progression is thought to be tied to chronic low-level type 1 inflammation originating in the adipose tissue during obesity; however, the specific immunological mechanisms regulating the progression of NAFLD-associated fibrosis in the liver are unclear. To investigate the immunopathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
92
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 56 publications
15
92
0
2
Order By: Relevance
“…IFN-γ has been shown to confer protection against chronic liver diseases. (21,22) Further, consistent with our in vivo observations, liver γδT cells mitigated CD4 + T-cell expression of IFN-γ in coculture experiments (Fig. 6E).…”
Section: γδT Cells Do Not Affect B-cell Phenotype In Sh But Modulate supporting
confidence: 89%
See 2 more Smart Citations
“…IFN-γ has been shown to confer protection against chronic liver diseases. (21,22) Further, consistent with our in vivo observations, liver γδT cells mitigated CD4 + T-cell expression of IFN-γ in coculture experiments (Fig. 6E).…”
Section: γδT Cells Do Not Affect B-cell Phenotype In Sh But Modulate supporting
confidence: 89%
“…We recently showed that γδT cells direct T‐helper cell effector function in cancer by checkpoint receptor ligation . Similarly, in the presence of γδT cells, hepatic CD4 + T cells lower levels of cytokines, such as IFN‐γ, that have protective roles in SH . Accordingly, our in vitro data show that hepatic γδT cells mitigate CD4 + T cell IFN‐γ production.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Consistently, increased production of IFN‐γ in intrahepatic NK cells was detected during MCD‐induced NASH (Figure C), and expression levels of IFN‐γ in the liver were significantly decreased upon the depletion of NK cells (Figure C). A recent study also reported the protective role of IFN‐γ in the NASH with obesity . However, the production of TGF‐β and IL‐10 was also upregulated in the intrahepatic NK cells (Figure C).…”
Section: Discussionmentioning
confidence: 54%
“…However, the production of TGF‐β and IL‐10 was also upregulated in the intrahepatic NK cells (Figure C). TGF‐β signalling in hepatocytes contributed to hepatocyte death and lipid accumulation via Smad signalling and ROS production that promoted the development of NASH and NASH progression to fibrosis . The roles of these cytokines should be further investigated to elucidate the mechanisms underlying the role of NK cells in NASH.…”
Section: Discussionmentioning
confidence: 99%